Indentured impressions: The embodied materiality of artistic practices in Mauritius - Baishali Ghosh (Journal of Indentureship and its Legacies)
This article ponders the ways contemporary Mauritius art negotiates the lives and afterlives of indentured labour histories and how artists explore visual, textual and sensorial materials to connect and counter their indentured ancestors’ narratives. The article aims to contribute to the epistemological and methodological scope of studying underrepresented visual and sensorial materials of indentured labour histories. It also reflects upon a decade-long engagement with Mauritian artists who are descendants of indentured labourers and who were involved in building a new identity following the independence of Mauritius in 1968. The first part of the text discusses how the artists appropriate colonial records, familial objects and sensorial evidences in executing their works and articulating their methods; it argues that the artistic praxes deliberately process embodied indentured labour histories. The second part thinks with and through a collaborative mural installed in the Renganaden Seeneevassen Building, a hub of government and corporate enterprises in Mauritius. It discusses how the mural can be understood as a critique of the stigmatization of the indentured labourers’ bodies and how it subverts the colonial gaze that tried to frame and limit indentured bodies. Reading the mural becomes a way to unravel colonial forms of spectatorship, and instead focus on how the artists voice their subaltern indentured ancestors and coeval communities.